2014
DOI: 10.1155/2014/854084
|View full text |Cite
|
Sign up to set email alerts
|

Median Nerve to Biceps Nerve Transfer to Restore Elbow Flexion in Obstetric Brachial Plexus Palsy

Abstract: Median nerve to biceps nerve transfer in the arm has been reported only in adults. The following paper reports on 10 cases of this transfer in obstetric brachial plexus palsy. All patients had upper palsy (ERb's or extended ERb's palsy) and presented to the author late (13–19 months of age) with poor or no recovery of elbow flexion. Following the nerve transfer, nine children recovered elbow flexion (a score of 6 in one child and a score of 7 in eight children by the Toronto scale). The remaining child did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…Studies comparing spinal accessory to suprascapular nerve transfer versus C5 nerve grafting show equivalent results [58,59]. Of the patients, 65-90 % demonstrate functional recovery with the Oberlin transfer [60][61][62]. There is insignificant data to assess isolated outcomes of triceps branch to axillary nerve transfer in children, as it is more commonly done in conjunction with other nerve transfers [63].…”
Section: Microsurgical Techniquesmentioning
confidence: 99%
“…Studies comparing spinal accessory to suprascapular nerve transfer versus C5 nerve grafting show equivalent results [58,59]. Of the patients, 65-90 % demonstrate functional recovery with the Oberlin transfer [60][61][62]. There is insignificant data to assess isolated outcomes of triceps branch to axillary nerve transfer in children, as it is more commonly done in conjunction with other nerve transfers [63].…”
Section: Microsurgical Techniquesmentioning
confidence: 99%
“… 6 The results are excellent and consistent. 5 , 9 However, it is obvious that such knowledge is still lacking to the primary health care providers for OBPI.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Qattan et al 28 reported their results in 10 patients with obstetric brachial plexus palsy. The preoperative AMS for elbow flexion ranged from 0--2.…”
Section: Transfer Of Median Nervementioning
confidence: 99%